Strategi Indonesia Menghadapi Rivalitas Global Melalui Reformulasi Doktrin Pertahanan Berbasis Asta Cita - Atmoko, Andriyan Wahyu Dwi; Bawanto, Arief Tri; Susilo, Tarsisius; Basuki, Tedy; Nugroho, Ig. Widi (Syntax Literate, 2025)
The rivalry between the United States, China, and Russia in the Indo-Pacific region increasingly underscores the global geopolitical shift toward competition over strategic resources, trade routes, and technological supremacy. The leadership models of these three major actors exhibit distinct characteristics: the America First doctrine emphasizing defense-industry protectionism, China’s technocratic model of technology-driven national mobilization, and Russia’s use of energy sovereignty as a geopolitical instrument. These leadership dynamics not only reshape the regional security architecture but also generate multidomain threats with direct implications for Indonesia’s national interests This study employs a qualitative-descriptive approach, framed by the theories of transformational leadership (Burns & Bass), adaptive leadership (Heifetz), and strategic military leadership. To map Indonesia’s objective conditions, a SWOT analysis is applied to identify strengths, weaknesses, opportunities, and threats in the formulation of the national defense doctrine. The findings reveal that Indonesia possesses notable advantages, including its geostrategic position, the warrior ethos of the TNI, and opportunities for regional cooperation. However, significant challenges remain, such as technological limitations and dependence on external defense industries. The study’s key recommendation is the necessity of re-charting Indonesia’s defense doctrine based on Asta Cita principles in an integrative manner: prioritizing defense-industry self-reliance, strengthening defense diplomacy, capitalizing on the demographic dividend, and consolidating maritime superiority. In doing so, Indonesia will not only be able to anticipate global rivalries but also reinforce the foundations of an adaptive defense posture in pursuit of the Indonesia Emas 2045 vision.